Factors influencing the ICT innovation process in small-medium enterprises: a conceptual framework / Nurul Atikah Kamaruddin - Kamaruddin, Nurul Atikah (Faculty of Business and Management, 2022)
The emergence of the digital economy has the potential to spur innovation, boost productivity, and improve societal quality of life. The increase in ICT users in Malaysia can be seen during the Covid-19 crisis. Due to social restrictions on economic activities, many businesses have shifted to online platforms. However, it differs from small-medium enterprises (SMEs) owned by vulnerable populations. Their businesses were underperforming during the Covid-19 crisis as they could not deal with the operational stress generated by Covid-19due to limited resources, resulting in poor company performance. Therefore, a conceptual model has been identified in this project on the factors that can lead SMEs to successfully innovate the processes of ICT in their businesses.